Genetic influences on athletic performance - North, K. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The elite athlete represents a highly complex phenotype, which reflects training, the desire to win, and perhaps most importantly, the individual`s genetic makeup. Variables such as the force-generating capacity of muscle fibres at high velocity, VO2max, anaerobic threshold, and the capacity of the individual to adapt to exercise training are all strongly genetically influenced. However the specific genes responsible are not known.